Evaluation of renal responsiveness to exogenous parathyroid hormone on the first and third days of life - Erdem, Gülşen; Tunçer, Müyesser; Saatçi, Ümit; Ciliv, Gönenç (The Turkish Journal of Pediatrics, 1982)
Renal responsiveness to PTE infusion was investigated by determining the urinary c-AMP and tubular phosphate reabsorption percentages in six full term and six premature male infants on the first and third days of life. The decreases in the TPR percentages in all infants after PTE infusion show that low PTH activity, in addition to low GFR, could be responsible for the hyperphosphatemia observed in the first days of life. Although the individual responses varied widely, the infants responded to PTE infusion with an increase in urinary excretion of c-AMP.